I'm already familiar with the trigonometric version of this substitution $ t = \tan \frac{\theta}{2} $ and it's geometrical derivation involving the unit circle found here. However, I'm not sure how the hyperbolic equivalents (shown below) are derived.

$$ t = \tanh \dfrac{\theta}{2} = \dfrac{\sinh \theta}{\cosh \theta + 1} = \dfrac{\cosh \theta - 1}{\sinh \theta} $$

$$ \cosh \theta = \dfrac{1+t^2}{1-t^2}, \ \sinh \theta = \dfrac{2t}{1-t^2}$$ At the bottom of the page, it refers to projecting the point $ (\cosh \theta, \sinh \theta)$ which is found on the right branch of a hyperbola onto the y-axis from the center $ (-1, 0) $ but I'm unsure of what this means.

Can anybody provide a geometrical take on deriving these?


Here is the hyperbola $(\cosh(\theta),\sinh(\theta))$ and the line from $(-1,0)$ to a point on the hyperbola projected on the $y$-axis. The coordinate of the point is $$ \left(0,\frac{\sinh(\theta)}{1+\cosh(\theta)}\right)=\left(0,\tanh\left(\frac\theta2\right)\right) $$

$\hspace{6mm}$enter image description here

If $t=\dfrac{\sinh(\theta)}{1+\cosh(\theta)}$, then $1-t^2=\dfrac{2}{1+\cosh(\theta)}$. Therefore, $$ \begin{align} \sinh(\theta)&=\dfrac{2t}{1-t^2}\\ \cosh(\theta)&=\dfrac{1+t^2}{1-t^2} \end{align} $$

  • $\begingroup$ Thanks so much for your help :) $\endgroup$ – Khallil Mar 8 '14 at 16:24

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.